Analysis of Errors in Paragraph Writing in English by Second Year Geography & History Students at University of Baghdad - Sawsan Saud Aziz (College of Education for Women, 2019)
This study focuses on the writing skill which is a social act .Students need to express themselves in writing, but students of History and Geography departments are poor in writing. This study aims at identifying and classifying the errors committed by the students, and then giving remedies. Writing can be considered as a channel or as a goal of language learning. Students learn to write in a foreign language. Writing as a goal basically focuses on the development of writing skills to fulfill such purposes as note-taking, summarizing, narrating, reporting and replying required for various real-life situation (Mechalakelli,2007) Students at Departments of Geography and History study English as a part of their syllabus requirement in the College of Education for Women. The researcher realizes that it is important to improve students' skills in writing because it is an important tool to their profession and for further education in the future. Therefore, this study is an attempt to evaluate the writing skills of the second class evening students (History and Geography)Departments. The students are asked to write a paragraph on topics based on their reading passages, chosen from their prescribed textbooks. They had been trained to construct a well- organized paragraph in their preparatory schools for three years until their graduation. Hence, the study attempts to find the students' errors in their writing in English.